Preparation method of composite hydrogel for repairing soft tissue and tendon-bone interface
The composite hydrogel with the loading of ZIF-8 on Ge MA hydrogel to coat Se NPs solves the problem of soft tissue and tendon-bone interface repair, realizes the stable release and antibacterial effect of Se NPs, and promotes the complex structure of the interface Reconstruction and cell growth, providing biocompatibility and anti-inflammatory effects.
Patent Information
- Application Number
- CN202411250537.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to effectively repair defects between soft tissue and tendon-bone interfaces, especially because the complex structure and high heterogeneity of soft tissues make it difficult to reconstruct and repair, and there is a risk of infection in the transplantation of autologous tissues.
Compound hydrogels coated with Se NPs with Ge l MA hydrogel loaded with ZIF-8, and spontaneous cracking of ZIF-8 in an acidic environment have stable release and antibacterial effects, and pass Ge l MA Biocompatibility promotes cell growth.
The stable release of Se NPs is achieved, which induces stem cell proliferation and differentiation, has anti-inflammatory and bactericidal effects, promotes the reconstruction of complex structures between soft tissue and tendon-bone interface, and provides good cell tissue growth conditions.
Smart Images

Figure CN119280486A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a composite hydrogel, in particular to a method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface, and belongs to the field of soft tissue or tendon-bone interface rupture repair materials. Background Art
[0002] At present, surgical operations such as car accidents, accidents, and geriatric diseases will cause soft tissue defects to a certain extent. How to efficiently repair soft tissue defects has always been a clinical pain point. Tissue defects caused by trauma often include a variety of soft and hard tissues such as bone, cartilage, skin, and muscle, as well as tendon-bone interface sites. Compared with bone tissue with uniform texture, soft tissue has a more complex structure, a higher degree of heterogeneity, and a wider range of mechanical moduli. Therefore, the reconstruction and repair of soft tissue is more difficult. The tendon-bone interface needs to connect soft and hard tissues, and its tissue structure is more complex, and it often needs to undertake multiple biological functions. The repair of the tendon-bone interface has always been a difficult and painful problem in clinical practice. At present, the commonly used treatment method for soft tissue defects and damaged parts of the tendon-bone interface in regenerative medicine is still autologous tissue transplantation. However, the source of materials for autologous tissue transplantation is single, and it may cause problems such as infection at the donor site, so it is urgent to develop a biological scaffold material that can be used for the repair of soft tissue and tendon-bone interface. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface, so as to solve the problem of difficulty in traditional soft tissue reconstruction and repair.
[0004] The technical solution of the present invention to solve the above technical problems is as follows: A method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface, comprising the following steps: Step (1), dissolving Se NPs and Zn(NO3)2·6H2O in deionized water at a mass ratio of 1:2970, and stirring thoroughly to obtain solution A;
[0005] Step (2), weighing 2-methylimidazole and dissolving it in deionized water at a mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole of 297:2873 to obtain solution B; mixing the solution B with the solution A, and adding NaOH at a mass ratio of Zn(NO3)2·6H2O to NaOH of 297:1-297:4, preferably 297:2, stirring and centrifuging, pouring out the supernatant, and repeatedly washing the solid with deionized water and drying to obtain white powder ZIF-8@Se NPs;
[0006] Step (3), dissolving the freeze-dried Gel MA in double distilled water containing lithium acylphosphinate at 45-55° C. in the dark to obtain a Gel MA solution, and treating aseptically to obtain a sterile Gel MA solution; dispersing ZIF-8@Se NPs in the sterile Gel MA solution and stirring in the dark to obtain the final product.
[0007] Based on the above technical solution, the present invention can also be improved as follows.
[0008] Further, the Se NPs are obtained by the following method: BSA and deionized water are added to a reaction flask, and then Na2SeO3 and mg vitamin C are added and mixed, and the mixture is reacted at room temperature for 10-20 minutes, and the color of the solution gradually turns red until Na2SeO3 is reduced to Se nanoparticles. After reacting for 1 hour, the solvent is removed by a rotary evaporator, and the product Se NPs are collected;
[0009] The amounts of BSA, deionized water, Na2SeO3 and vitamin C were calculated by adding 160 mg BSA and 75 mL deionized water to a reaction flask, and then adding 34.6 mg Na2SeO3 and 211.2 mg vitamin C to mix.
[0010] Furthermore, the Gel MA is obtained by the following method: weigh gelatin and dissolve it in a first PBS solution at 50-70°C to obtain a gelatin solution, wherein the mass volume ratio of the two is 1:10; then weigh methacrylic anhydride and use a syringe pump to drop it into the gelatin solution at a rate of 0.3-0.8 mL / min, react for 1-3 hours, add a second PBS solution preheated to 50-70°C, continue stirring for 20-60 minutes and stop, use a dialysis bag to purify with deionized water for 5-7 days, and change the water 1-3 times; after the dialysis is completed, centrifuge the product at 8000-12000rm, collect the supernatant; freeze-dry the supernatant using a vacuum freeze dryer to obtain the product Gel MA, wherein the volume ratio of methacrylic anhydride to PBS solution is 1.6:10; and the volume ratio of the first PBS solution to the second PBS solution is 1:4.
[0011] Furthermore, the aseptic treatment in step (3) is obtained by filtering the Ge l MA solution through a 0.22 μm membrane.
[0012] Further, in step (2), the drying is carried out in an oven at 40° C. for 12 hours.
[0013] Furthermore, in step (2), the stirring centrifugation is maintained at 250 rpm, the stirring reaction is carried out for 24 hours, and the centrifugation is carried out at 8000-12000 rm.
[0014] Furthermore, in step (3), the mass volume ratio of the lithium acylphosphinate salt to double distilled water is 0.2% w / v.
[0015] Furthermore, the mass volume ratio of the freeze-dried Gel MA to the double distilled water containing the lithium acylphosphinate salt is 1:1.
[0016] Furthermore, the mass volume concentration of the ZIF-8@Se NPs and the sterile Gel MA solution is 0.05-0.2%.
[0017] The invention uses Ge l MA hydrogel to load ZIF-8 to coat Se NPs to obtain ZIF-8@Se NPs particles. The characteristic of ZIF-8 cleavage and release in an acidic environment can realize the stable and continuous release of Se NPs in vivo. SeNPs of different concentrations can induce stem cells to proliferate and differentiate into different cells, which is beneficial to the reconstruction of the complex structure of the damaged part of the soft tissue and tendon-bone interface. In addition, the spontaneous cleavage of ZIF-8 in an acidic environment can produce Zn 2+ ions, and Zn 2+ ZIF-8 has certain antibacterial properties. Degradation of ZIF-8 will also produce imidazole substances, which are essential nutrients for organisms. Due to the characteristics of ZIF-8, the prepared composite hydrogel material can play an anti-inflammatory and bactericidal effect in the process of tendon-bone interface repair and is beneficial to the recovery of damaged areas. Ge l MA hydrogel also provides good conditions for the growth of cell tissues in damaged areas due to its excellent biocompatibility and biological functional properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 (A) XRD and (B) FT-IR analysis results of ZIF-8@Se NPs of the present invention;
[0019] Figure 2 (C) SEM (D) particle size (E) EDS analysis results of ZIF-8@Se NPs of the present invention;
[0020] Figure 3 This is a diagram showing the cytotoxicity test results of ZIF-8@Se NPs of the present invention;
[0021] Figure 4 (A) SEM and EDS analysis results of Ge l MA / ZIF-8@Se NPs of the present invention;
[0022] Figure 5 (B) rheology, (C) compression modulus, and (D) I CP selenium ion precipitation analysis results of the Ge l MA / ZI F-8@Se NPs of the present invention;
[0023] Figure 6The CCK-8 results of the co-culture of the Ge l MA / ZIF-8@Se NPs composite hydrogel of the present invention with human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) for 1 day and 3 days;
[0024] Figure 7 The figure is the result of staining of dead cells after the GelMA / ZIF-8@Se NPs composite hydrogel of the present invention was co-cultured with human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) for 1 day;
[0025] Figure 8 This is a diagram showing the cytoskeleton staining results of the co-culture of the Ge l MA / Z IF-8@Se NPs composite hydrogel of the present invention with human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) for 1 day. DETAILED DESCRIPTION
[0026] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0027] Materials used in the embodiments of the present invention: bovine serum albumin (BSA), sodium selenate (Na2SeO3), ascorbic acid / vitamin C, 2-methylimidazole, zinc nitrate hexahydrate, sodium hydroxide, gelatin, methacrylic anhydride (MA), lithium acylphosphite (LAP), deionized water (DI H2O), phosphate buffered saline (PBS)
[0028] Example 1
[0029] Preparation of ZIF-8@Se NPs: First, 160 mg BSA and 71 mL deionized water were added to a reaction flask, and then 1 mL Na2SeO3 (0.2 M) and 3 mL vitamin C (0.4 M) solutions were added. The mixture was reacted at room temperature for 15 minutes, and the color of the solution gradually turned red, indicating that Na2SeO3 was reduced to Se nanoparticles. After 1 hour of reaction, the solvent was removed by a rotary evaporator and the product Se nanoparticles (Se NPs) were collected; 2.873 g 2-methylimidazole was weighed into a beaker, and 10 mL deionized water was added, and it was placed on a magnetic stirrer at room temperature to dissolve to obtain a clear solution A, and then 0.297 g Zn(NO3)2·6H2O was weighed and placed in a test tube containing 18 mL deionized water. After shaking and dissolving, solution B was obtained. Finally, solution B was mixed with solution A and 0 g, 0.2 g or 0.4 g NaOH was added. The reaction was stirred at 250 rpm for 24 hours. Centrifuge at 10,000 rpm, pour out the supernatant, and wash the solid repeatedly with deionized water three times. Finally, put it in an oven at 40°C and dry it for 12 hours to obtain a white powder, which is Z IF-8@SeNPs.
[0030] Preparation of Ge l MA / ZI F-8@Se NPs: 10 g gelatin was weighed and dissolved in 100 mL PBS solution at 60 ° C and stirred for 1 h; 16 mL methacrylic anhydride (MA) was weighed and added to the gelatin solution at a rate of 0.5 mL / min using a syringe pump. After reacting for 2 h, 400 mL PBS solution preheated to 60 ° C was added, and stirring was continued for 30 min before stopping. The mixture was purified with deionized water using a dialysis bag for 5-7 days, and the water was changed twice a day; after the dialysis was completed, the product was centrifuged at 10000 rm for 5 min and the supernatant was collected; the supernatant was freeze-dried using a vacuum freeze dryer to obtain the product Ge l MA; the freeze-dried Ge l MA (0.1 g) was dissolved in DI H2O (1.0 mL) containing lithium acylphosphite (LAP) salt (0.2% w / v) at 50 ° C in the dark; then, a sterile Ge l MA solution was prepared by filtration through a 0.22 μm membrane; different amounts of sterile Z IF-8@Se NPs were dispersed into sterile Gel MA solution, and the mass volume concentration of ZI F-8@Se NPs in sterile Gel MA solution was 0.05, 0.1, and 0.2% w / v; stirred at 40°C in the dark for 12 h to produce GZ-0.5, GZ-1, and GZ-2, respectively.
[0031] 1. Physical and chemical characterization detection method of ZIF-8@Se NPs obtained in Example 1:
[0032] X-ray diffraction (XRD, D8 Discover) and Fourier transform infrared spectroscopy (FTIR, ThermoScientific Nico l et 6700) were used for composition characterization; scanning electron microscopy (SEM, Nova NanoSEM450), transmission electron microscopy (TEM) and laser scattering particle size distribution analyzer (LPSA, LA960A2) were used to analyze the structural characteristics and particle size distribution of ZI F-8@Se NPs. Figure 1 As shown in the figure, through the analysis of XRD results, we can observe the characteristic peaks (011), (002), (112) and (022) in the XRD spectrum, which shows that we have successfully prepared ZI F-8@Se NPs particles. It is consistent with the results of FT-IR spectrum. In addition, Figure 2SEM and EDS showed that with the increase of NaOH, the regular dodecahedral structure of ZIF-8 became more regular, the surface structure became smoother, and the size of ZIF-8 also decreased; Se NPs were mostly coated by ZIF-8, and a small amount was adsorbed on the surface of ZIF-8; according to EDS results, with the increase of NaOH, the content of Se NPs coated by ZIF-8 will gradually decrease, which may be due to the reduction of ZIF-8 size, resulting in a reduction in internal space. Combined with application analysis, the best ratio is the ratio of adding 0.2g NaOH.
[0033] 2. Cytotoxicity experimental method of ZIF-8@Se NPs obtained in Example 1:
[0034] Human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) were co-cultured with ZI F-8@SeNPs (0.05, 0.1, 0.2% w / v) as Se-1, Se-2, and Se-3 groups in DMEM medium at 37°C and 5% CO2. To evaluate the biocompatibility of ZI F-8@Se NPs, the cells were collected after 1 day of co-culture and treated with CCK-8 reagent, and the results were analyzed, as shown in Figure 2. Figure 3 As shown in the figure, the CCK-8 results after co-culturing human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) with different concentrations of SeNPs for 1 day showed that Se NPs had good biocompatibility for both cells and had a certain promoting effect on cell proliferation, which was more obvious in BMSCs cells. In addition, as the concentration of Se NPs changed, the promoting effect on cell proliferation also changed accordingly.
[0035] 3. Experimental methods for preparation and physicochemical characterization of GelMA / ZIF-8@Se NPs composite hydrogel obtained in Example 1:
[0036] Lyophilized Gel MA (0.1 g) was dissolved in DI H2O (1.0 mL) containing lithium acylphosphite (LAP) salt (0.2% w / v) at 50 °C in the dark. Then, sterile Gel MA solution was prepared by filtration through a 0.22 μm membrane. Subsequently, different amounts of sterile ZIF-8@Se NPs (0.05, 0.1, 0.2% w / v) were dispersed into the sterile Gel MA solution according to the effect of ZIF-8NP concentration on cell proliferation. After stirring at 40 °C in the dark for 12 h, GZ-0.5, GZ-1, and GZ-2 were produced after irradiation with 450 nm UV light for 30 s, as shown in Figure 2. Figure 4 , 5As shown in the figure, the Gel MA / ZI F-8@Se NPs composite hydrogel was prepared, and its micromorphology, rheological properties and tensile test were tested. Through SEM, it can be observed that the obtained hydrogel has good porosity, which provides a place for cell proliferation. The rheological results show that with the addition of ZI F-8@Se NPs, the viscoelasticity of the Gel MA hydrogel is improved, which is closer to the viscoelasticity of the growth environment of tendon cells in the body; as expected, the addition of ZI F-8@Se NPs can effectively improve the mechanical properties of the Gel MA hydrogel and better meet the requirements of the biomechanical functions required by the rotator cuff.
[0037] 4. Example 1: Biocompatibility experimental method for obtaining GelMA / ZI F-8@Se NPs composite hydrogel:
[0038] Human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) were co-cultured with GZ-0.5, GZ-1 and GZ-2 in DMEM medium at 37°C and 5% CO2. To evaluate the biocompatibility of Gel / ZIF-8@SeNPs hydrogel, cells were collected after 1d and 3d of co-culture, treated with CCK-8 reagent, and the results were analyzed. To observe the live and dead status of cells, cells were collected after 1d and 3d of co-culture, treated with cell live and dead staining kit, and the results were analyzed. Figure 6 Human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) were co-cultured with GZ-0.5, GZ-1 and GZ-2 hydrogels for 1d and 3d. The cells were treated with CCK-8 kit according to the instructions. The results showed that the Gel MA composite hydrogel had good biocompatibility for both cells, and with the increase of co-culture time, it could promote cell proliferation to a certain extent, which was more obvious in BMSCs cells. Figure 5 After treating the cells co-cultured for 1 day with a cell live-dead staining kit, the results also showed that the Ge l MA composite hydrogel had good biocompatibility.
[0039] 5. Cytoskeleton staining experiment of Ge l MA / Z IF-8@Se NPs composite hydrogel
[0040] Human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) were co-cultured with GZ-0.5, GZ-1 and GZ-2 in DMEM medium at 37°C and 5% CO2. To evaluate the effect of Gel / Z IF-8@SeNPs hydrogel on cell growth, cells were collected after 1 day of co-culture and treated with FITC phalloidin kit. The results are shown in Figure 2. Figure 7 and Figure 8 After human bone marrow mesenchymal stem cells (BMSCs) and rabbit tendon stem cells (TSCSs) were co-cultured with GZ-0.5, GZ-1 and GZ-2 hydrogels for 1 day, the cells were treated with FTIR phalloidin kit according to the instructions. The results showed that Ge l MA composite hydrogel can increase the spreading area of TSCSs cells, which is conducive to better cell growth; but the performance for BMSCs cells is not obvious. This may be related to the appropriate growth conditions of cells. Tendon stem cells are mainly present in the tendon part in the body, and their elasticity is closer to that of Ge l MA composite hydrogel, so they are more suitable for growth. Changes in the content of ZIF-8@Se NPs have little effect on cell spreading. The above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface, characterized in that: The following steps are involved: Step (1), dissolving Se NPs and Zn(NO3)2·6H2O in deionized water at a mass ratio of 1:2970, and stirring thoroughly to obtain solution A; Step (2), weighing 2-methylimidazole and dissolving it in deionized water at a mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole of 297:2873 to obtain solution B; mixing the solution B with the solution A, and adding NaOH at a mass ratio of Zn(NO3)2·6H2O to NaOH of 297:1-297:4, stirring and centrifuging, pouring out the supernatant, and repeatedly washing the solid with deionized water and drying to obtain white powder ZIF-8@Se NPs; Step (3), dissolving the freeze-dried GelMA in double distilled water containing lithium acylphosphinate at 45-55° C. in the dark to obtain a GelMA solution, and aseptically treating to obtain a sterile GelMA solution; The ZIF-8@Se NPs were dispersed in sterile GelMA solution and stirred in the dark to obtain the final product.
2. A method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to claim 1, characterized in that: The Se NPs are obtained by the following method: BSA and deionized water are added to a reaction flask, and then Na2SeO3 and vitamin C are added and mixed, and the mixture is reacted at room temperature for 10-20 minutes, and the color of the solution gradually turns red until Na2SeO3 is reduced to Se nanoparticles. After reacting for 1 hour, the solvent is removed by a rotary evaporator, and the product Se NPs are collected; The amounts of BSA, deionized water, Na2SeO3 and vitamin C were calculated by adding 160 mg BSA and 75 mL deionized water to a reaction flask, and then adding 34.6 mg Na2SeO3 and 211.2 mg vitamin C to mix.
3. A method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to claim 1, characterized in that: The GelMA is obtained by the following method: weighing gelatin and dissolving it in a first PBS solution at 50-70°C to obtain a gelatin solution, wherein the mass volume ratio of the two is 1:10; then weighing methacrylic anhydride, using a syringe pump to dropwise add it to the gelatin solution at a rate of 0.3-0.8 mL / min, reacting for 1-3 hours, adding a second PBS solution preheated to 50-70°C, continuing to stir for 20-60 minutes and then stopping, using a dialysis bag to purify with deionized water for 5-7 days, and changing the water 1-3 times; after the dialysis is completed, centrifuging the product at 8000-12000rm, collecting the supernatant; freeze-drying the supernatant using a vacuum freeze dryer to obtain the product GelMA, wherein the volume ratio of the methacrylic anhydride to the PBS solution is 1.6:10; and the volume ratio of the first PBS solution to the second PBS solution is 1:
4.
4. The method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to claim 1, characterized in that: The aseptic treatment in step (3) is obtained by filtering the GelMA solution through a 0.22 μm membrane.
5. The method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to claim 1, characterized in that: Step (2), drying in an oven at 40° C. for 12 hours.
6. The method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to claim 1, characterized in that: In step (2), the stirring centrifugation is maintained at 250 rpm, the stirring reaction is carried out for 24 hours, and the centrifugation is carried out at 8000-12000 rm.
7. A method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to claim 1, characterized in that: The mass volume ratio of the lithium acylphosphinate salt to double distilled water in step (3) is 0.2% w / v.
8. The method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to claim 1, characterized in that: The mass volume ratio of the freeze-dried GelMA to the double distilled water containing the acylphosphinate lithium salt is 1:
1.
9. A method for preparing a composite hydrogel for repairing soft tissue and tendon-bone interface according to any one of claims 1 to 8, characterized in that: The mass volume concentration of the ZIF-8@Se NPs and the sterile GelMA solution is 0.05-0.2%.